Comprehensive two dimensional gas chromatographic separation of fatty acids methyl esters with online reduction. Issue 11 (November 2014) - Delmonte, Pierluigi; Kramer, John K.G.; Hayward, Douglas G.; Mossoba, Magdi M.; Fardin‐Kia, Ali Reza; Aldai, Noelia
Abstract : The accurate analysis of complex fats and oils often requires combining data from multiple GC separations, fractionation by LC prior to GC analysis, and identifying fatty acids or confirming their identities by mass spectrometry and synthetic reference materials. Comprehensive two dimensional gas chromatography markedly increases the number of resolved fatty acid methyl esters (FAME) in a single separation experiment by combining the separations of two capillary columns. The addition of a capillary reducer in front of the second capillary column provides unique separation patterns and structural information for fatty acids based on simple elution rules.